Left-sided Approach for Cardiac Procedure and Thoracoplasty in a Patient with Marfan Syndrome - Shimamura, J.; Kubota, H.; Sudo, K. (The Thoracic and Cardiovascular Surgeon, 2012)
We present a case of a 20-year-old female in whom we successfully performed a simultaneous Bentall procedure and thoracoplasty by initially removing only the left side of the costal cartilages. This modified sternal elevation technique offered chest stability and an excellent surgical view, and the postoperative course was satisfactory.
Keywords: thoracoplasty; Bentall procedure; Marfan syndrome; sternal elevation; chest deformities